Avaliação da ocorrência de eventos adversos em um centro de terapia intensiva adulto - Beck, Andrea Diez (Universidade do Vale do Rio dos Sinos, 2014)
Health organizations are the settings that host sectors, activities and processes whose complexity favors the occurrences of adverse events (AE). As a way to avoid them, the incorporation of substantial and adequate modifications arises as a basic need to improve patient’s safety. OBJECTIVE: To track the occurrences of adverse events on the Intensive Care Center, applying the suggested approach by the Institute for Healthcare Improvement. MATERIAL AND METHOD: Transversal study and analytical performed at the Intensive Care Center in a big private philanthropic hospital in the city of Porto Alegre/RS. 128 medical records from patients who were discharged from the hospital between april and october in the year 2012 were randomly analyzed by stratification and proportion. It was also included patients who were more than 18 years old and that had been at least 24 hours in the Intense Care Unit, independently from the outcome of discharged and excluded patients who were under rehabilitation and psychiatric hospitalization. The data was collected by two nurses and an intensivist doctor, who authenticated the collected data, defined the adverse events and the damage. The checking protocol of each medical record happened in the recommended time of 20 minutes. The data was classified in the patterns of Intensive Therapy and Care: (a) C1: blood transfusion or the use of hemocomponents; (b) C2: cardiorespiratory arrest; (c) C5: XR or ultrasound with Doppler to study emboli or deep venous thrombosis (TVP); (d) I3 procedure: (e) I4: intubation / reintubation; (f) others. The damages were classified according to the inclusion and exclusion categories. The variable was described by absolute and relative frequencies. The qualitative variables were describe by absolute and relative frequencies and the quantitative by mean and standard deviation. Chi-square test was used in order to test the associations between the qualitative variables. The ttest was employed to compare means between the groups. For all analyses, the significance level was 5%. The project was approved research ethics committee by the institutions. RESULTS: 39,8 of the medical records were identified with some AE within an average of 0,8 events per medical record. The main reason to hospitalization in Intensive Care was the postoperative. The patients who suffered AE had longer time remaining at the ICU (p<0,001). 51 patients were identified with AE whose 40 AE were tracked in the care module and in the intensive therapy, identified by 241 triggers, and 60 AE were identified by other trackers suggested as tools from the IHI. In 56% of the cases, the AE were classified as temporary damage and there was a need of an intervention in the patient. Around 15% of the cases had damage that there was a need of an intervention to keep them alive or they died. The preventable AE happened in 77% of the cases. CONCLUSION: The AE acknowledgment may contribute and direct improvement strategies and search of results, considering that three alternatives were listed to the implementation of short to medium term in the intensive care. They are: (1) checklist; (2) creation of a continued education program and certification to the nursery professionals in the intensive care; (3) Implementation of a method to evaluate systematically the medical records from patients who are hospitalized in the adult IC.
Keywords: Terapia intensiva; Erros médicos; Segurança do paciente; Garantia da qualidade dos cuidados de saúde; Qualidade da assistência à saúde; Intensive care; Medical errors; Patient safety; Quality assurance health care; Quality in health care; ACCNPQ::Ciências da Saúde::Enfermagem